Hypersensitive esophagus: can it be classified as a subgroup of gastroesophageal reflux disease? - Sedef ÖZDAL KURAN; Ülkü DAĞLI; Canan ALKIM; Dilek OĞUZ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-